Evaluation of the Genotoxic Potential of the Selective COX-2 Inhibitor Enflicoxib in a Battery of in vitro and in vivo Genotoxicity Assays - Guzmán, Antonio; Homedes, Josep; Salichs, Marta (Drug Research, 2022)
Aim Enflicoxib, a selective COX-2 inhibitor approved for the treatment of pain and inflammation associated with osteoarthritis in dogs (Daxocox® [Ecuphar/Animalcare Group]) was assessed for its genotoxic potential in a battery of in vitro and in vivo genotoxicity assays. These comprised a bacterial reverse mutation assay (Ames test), an in vitro human lymphocyte chromosome aberration assay and an in vivo mouse bone marrow micronucleus assay.Methods Relevant vehicle and positive control cultures and animals were included in all assays. In the Ames test, enflicoxib was tested at concentrations of up to 5000 μg/plate. Signs of cytotoxicity were observed at the highest tested concentrations for several of the bacterial strains, both in absence and presence of S9. In human lymphocytes, enflicoxib was assessed for the induction of chromosomal aberrations when exposed at concentrations of up to 62.5 (3 hours) and 29.6 µg/mL (20 hours) in the absence of S9, and up to 66.7 µg/mL (3 hours) in presence of S9. Signs of cell toxicity, evidenced as a decrease in the mitotic index, were observed at these concentrations. In the mouse micronucleus assay, enflicoxib dose levels of up to 2000 mg/kg were administered (single dose) to male and female animals, and bone marrow samples were taken 24 and 48 hours (high-dose animals only) after administration.Results Enflicoxib was shown to lack genotoxic activity in the conducted assays.Conclusions The administration of enflicoxib as a therapeutic analgesic agent would not pose a genotoxic risk to animals or humans.
Keywords: Enflicoxib; Daxocox; Genotoxicity; Mutagenesis; COX-2